Multicoloured mayhem : parenting the many shades of adolescents and children with autism, Asperger syndrome, and AD/HD - Jackson, Jacqui (Jessica Kingsley Publishers, 2004)
Jacqui Jackson has seven children. Luke (author of Freaks, Geeks and Asperger Syndrome) has Asperger Syndrome, Joe has ADHD, and Ben has autism. Life is anything but straightforward, but the chaos of the Jacksons' lives is threaded through with humor and common sense. Full of anecdotes and lively thinking, the book explains vividly what it is like to parent young people with such a range of conditions, and provides a wealth of helpful and creative advice for other parents and carers. Anyone who has wondered what life in such a family might be like will be fascinated.